Rekonstruksi Dakwah Islam di Ranah Politik dan Kultural - Abdullah Hakam Shah; Rizqi Maulida Amalia (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
In Indonesia, da'wah in the political and cultural spheres is compared to siblings who have not spoken to one another in a long time, contradicting one another and even bringing one another down. Reconstruction of da'wah in Indonesia's political and cultural realms is an extremely interesting subject that has the potential to constantly evolve and present new breakthroughs. Legislation and public policy issues require these individuals to engage in the political process, whereas social-social issues typically require a cultural approach. The purpose of this study is to determine whether it is true that Islamic da'wah in the political and cultural realms cannot coexist, particularly in the Indonesian context, and whether it is possible to create synergy – even convergence – between political and cultural da'wah, as well as what compromises must be made with mainstream circles. Today, political and cultural da'wah circles exist in Indonesia. By utilizing a literature-based approach that incorporates both theory and expert opinion. Additionally, it is analyzed by providing interpretations that are transformed into objects that can be interpreted in terms of space and time. The article concludes that, in contemporary Indonesia, the synergy between political and cultural da'wah must be directed toward resolving the nation's problems, such as poverty and ignorance eradication, upholding justice, and establishing a clean government. These efforts should be couched in a framework of noble morality, elegant strategy, and an approach that is both friendly and sympathetic.Keywords: Reconstruction; Islamic Education; Politics, Culture AbstrakDakwah di ranah politik dan kultural di Indonesia digambarkan seolah-olah sebagai siblings yang sudah lama tidak saling menyapa, kontradiktif, bahkan saling menjatuhkan. Rekontruksi dakwah di ranah politik dan kultural di Indonesia merupakan topik yang sangat menarik dan memiliki potensi kuat untuk selalu berkembang serta menghadirkan terobosan baru. Persoalan perundang-undangan dan kebijakan-kebijakan publik mengharuskan umat ini untuk terlibat di arena politik, sementara persoalan sosial-kemasyarakatan cenderung menghajatkan pendekatan kultural. Penelitian ini hendak menjawab pertanyaan, benarkah dakwah Islam di ranah politik dan di ranah kultural tidak bisa dipertemukan, khususnya dalam konteks Indonesia dan mampukah menciptakan sinergi –bahkan konvergensi—antara dakwah politik dan dakwah kultural serta Apa saja kompromi-kompromi yang mesti ditempuh dari mainstream kalangan dakwah politik dan kalangan dakwah kultural yang ada di Indonesia sekarang. Dengan menggunakan pendekatan literatur yang mempertimbangkan teori serta pendapat para ahli. Selanjutnya dianalisis dengan cara memberikan interprestasi yang menjadi obyek untuk ditafsirkan dalam kontek ruang dan waktu. Artikel ini menemukan bahwa dalam konteks Indonesia kontemporer, sinergi antara dakwah politik dan dakwah kultural tersebut mesti diarahkan untuk menyelesaikan problematika bangsa seperti pengentasan kemiskinan dan kebodohan, penegakan keadilan, serta pembentukan pemerintahan yang bersih. Upaya-upaya ini hendaknya dikemas dalam bingkai moralitas yang luhur, strategi yang elegan, serta cara pendekatan yang ramah dan simpatik.Keywords: Rekonstruksi; Dakwah Islam; Politik, Kultural